“La lectoescritura en el aprendizaje de los estudiantes de tercer grado de Educación Básica”. - Reyes Chancay, Leonor Rosario (2021)
The following research took as its starting point the research problem How to improve literacy learning in third grade students of Basic Education at the Víctor Manuel Rendón school?, Proposing as a general objective: Develop a methodological strategy for the improvement of the Literacy in third grade students of Basic Education. The research is guided by the mixed approach, and assumes applied research aimed at transforming reality and uses the scientific method and research techniques that allowed the diagnosis of the literacy levels presented by third-grade students of education. Basic of the Víctor Manuel Rendón School, which will come to know the main insufficiencies and justify the proposed methodological strategy for their solution; The partial application of the methodological strategy of literacy for students of the third grade of Basic Education was viable and feasible as long as significant preliminary results are achieved, demonstrating the relevance to the solution of the research problem from which the present investigation is based.